THE "UPPER POOL," ITS "CONDUIT," AND "THE ROAD OF THE FULLER'S FIELD" IN EIGHTH CENTURY BC JERUSALEM AND THEIR SIGNIFICANCE FOR THE POOLS OF BETHESDA AND SILOAM - von Wahlde, Urban (Revue biblique, 2006)
Recent studies have argued that the Upper Pool referred to in 2 Kings 18:17 and Isaiah 7:3 and 36:1-3 refers to the northern basin of the Pool of Bethesda rather than to a pool near the southern tip of the City of David, in the area of the Pool of Siloam. Close examination of these arguments in connection with recent archaeological discoveries indicates that this view is incorrect and that a southern location for the Pool, its Conduit, and the Road of the Fuller's Field fits both the literary and the archaeological data better and is the correct view. De récentes études suggèrent que la piscine supérieure de 2 R 18,17 et Is 7,3 & 36, 1-3, soit le bassin nord de la piscine de Béthesda, plutôt qu'une piscine vers l'extrémité sud de la ville de David, aux environs de Siloé. Un examen de l'argumentation, et des résultats archéologiques récents, rendent l'hypothèse Béthesda caduque. Un emplacement au sud s'impose pour la piscine supérieure, son canal et le chemin du champ du Foulon.